Identification and characterization of a Mef2 transcriptional activator in schistosome parasites. - John N Milligan; Emmitt R Jolly (Public Library of Science (PLoS), 2012)
Myocyte enhancer factor 2 protein (Mef2) is an evolutionarily conserved activator of transcription that is critical to induce and control complex processes in myogenesis and neurogenesis in vertebrates and insects, and osteogenesis in vertebrates. In Drosophila, Mef2 null mutants are unable to produce differentiated muscle cells, and in vertebrates, Mef2 mutants are embryonic lethal. Schistosome worms are responsible for over 200 million cases of schistosomiasis globally, but little is known about early development of schistosome parasites after infecting a vertebrate host. Understanding basic schistosome development could be crucial to delineating potential drug targets. Here, we identify and characterize Mef2 from the schistosome worm Schistosoma mansoni (SmMef2). We initially identified SmMef2 as a homolog to the yeast Mef2 homolog, Resistance to Lethality of MKK1P386 overexpression (Rlm1), and we show that SmMef2 is homologous to conserved Mef2 family proteins. Using a genetics approach, we demonstrate that SmMef2 is a transactivator that can induce transcription of four separate heterologous reporter genes by yeast one-hybrid analysis. We also show that Mef2 is expressed during several stages of schistosome development by quantitative PCR and that it can bind to conserved Mef2 DNA consensus binding sequences.